2002
DOI: 10.1172/jci7272
|View full text |Cite
|
Sign up to set email alerts
|

Protective immunity against atherosclerosis carried by B cells of hypercholesterolemic mice

Abstract: Atherosclerosis is characterized by vascular inflammation and associated with systemic and local immune responses to oxidized LDL (oxLDL) and other antigens. Since immunization with oxLDL reduces atherosclerosis, we hypothesized that the disease might be associated with development of protective immunity. Here we show that spleen-associated immune activity protects against atherosclerosis. Splenectomy dramatically aggravated atherosclerosis in hypercholesterolemic apoE knockout (apoE°) mice. Transfer of spleen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
135
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 451 publications
(154 citation statements)
references
References 39 publications
8
135
0
2
Order By: Relevance
“…76 In line with these data, reconstitution of irradiated Ldlr −/− with B cell-deficient bone marrow has been shown to worsen atherosclerosis. 77 Another study suggested that the lack of B1a cells and the consequent lowering of IgM was responsible for the deleterious effects of B-cell deficiency.…”
Section: Role Of B Cells In Atherosclerosismentioning
confidence: 74%
“…76 In line with these data, reconstitution of irradiated Ldlr −/− with B cell-deficient bone marrow has been shown to worsen atherosclerosis. 77 Another study suggested that the lack of B1a cells and the consequent lowering of IgM was responsible for the deleterious effects of B-cell deficiency.…”
Section: Role Of B Cells In Atherosclerosismentioning
confidence: 74%
“…[25][26][27][28] Initial studies 1,29,30 indicated the atheroprotective potential of the B-cell compartment that relies on B1a cells and germ-line-encoded immunoglobulins. In contrast, recent studies have identified T-dependent B cells (B2 cells) as potent proatherogenic mediators in the ApoE° and low-density lipoprotein receptor-knockout mouse models.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hypertensive patients with high percentages of CD40 + B cells were at lower risk for stroke,22 whereas high numbers of CD86 + B cells showed higher risk for stroke 22. A larger body of evidence is derived from elaborate mouse studies, which identified a subset‐specific role for B lymphocytes in atherosclerosis 23, 24, 25. To date, it is generally accepted that (auto)antibody‐producing B1 B cells are atheroprotective26, 27 and this protective effect depends on IgM secretion,28 whereas conventional B2 B cells are generally considered proatherogenic 29.…”
Section: Introductionmentioning
confidence: 99%